Meat Traits of Muscovy Ducks Fed on Phytonutrition Meal - Ali , Muhamad; Sukirno; Tamzil, Muhamad Hasil; Ichsan, Muhamad (International Journal of Poultry Science, 2014)
Animal products with high fat content are generally correlated with several human diseases including coronary heart disease, hypertension and arteriosclerosis. However, some unsaturated fatty acids are considered to have pivotal role in human health. As a consequence, many studies were conducted to reduce fat and increase some unsaturated fatty acid content in animal products. This study investigated the use of phytonutrition (duckweed) as feed ingredient on fat and fatty acids composition of Muscovy duck (Cairina moschata domestica L.) meat. Results showed that the use of 1% duckweed significantly increased the linoleic acid content of carcass while reducing the fat level. This result might suggest that duckweed can be used as an alternative feed ingredient to produce a healthy poultry meat.